SERUM LEPTIN LEVELS IN PATIENTS WITH CORONARY ARTERY DISEASE - Akram, Shama; Ahmed, Zamir; Fayyaz, Iram; Mehmood, Sadia; Ghani, Mansoor; Choudhary, Anbreen Mazhar; Shah, Imran (Journal of Ayub Medical College Abbottabad, 2011)
Background: Cardiovascular diseases (CVD) are the leading cause of morbidity, mortality and disability worldwide. Leptin, a 16kDa product of ob gene, is an endocrine hormone produced by white adipose tissue. It is primarily involved in the regulation of food intake and energy expenditure. Hyperleptinemia is one of the novel risk factors contributing in many ways to CVD. Objective: The objective of the study was to find the level of leptin in patients with coronary artery disease (CAD) and compare it with healthy people in our population. Methods: Our study was an analytical and crosssectional study. Our study included 60 patients with a history of CAD and 60 healthy controls (aged 40-60 years, both sexes). Leptin levels were measured by ELISA. Results: Mean serum leptin level in patients was 11.48±11.25 Î·g/ml, while control group had a mean leptin level of 8.22±8.01 Î·g/ml (p=0.071). Conclusion: Leptin levels were higher in patients but the difference was non-significant. More studies are needed with larger sample size in our population. Keywords: Coronary Artery Disease (CAD), Leptin